Odpowiedzi

2010-01-12T14:04:23+01:00
A)
2x - 2y = 7
4x + 3y = 21

2x = 7 + 2y
4x + 3y = 21

2x = 7 + 2y
14 + 4y + 3y = 21

2x = 7 + 2y
7y = 7 / ÷ 7

2x = 7 + 2y
y = 1

2x= 7 +2
y = 1

2x = 9
y = 1

x = 4,5
y = 1


C)
2x + 3y = 14
3x - 2y = 8

2x = 14 - 3y
14 - 3y + 7 - 1,5y - 2y = 8

2x = 14 - 3y
-6,5y = -13 /÷ (-6,5)

2x = 14 - 3y
y = 2

2x = 14 - 6
y = 2

2x = 8 / ÷ 2
y = 2

x = 4
y = 2

D)
½x - 2y = 8
2x + 5y = 6

½x = 8 + 2y
32 + 8y + 5y = 6

½x = 8 + 2y
13y = -26 / ÷ 13

½x = 8 + 2y
y = -2

½x = 8 - 4
y = -2

½x = 4 / ÷ ½
y = -2

x = 8
y = -2